Posterior tibial slope and anterior post-cam contact can change knee kinematics in extension in bi-cruciate stabilized total knee arthroplasty. Issue 11 (1st November 2020) - Hada, Masaru; Mizu-uchi, Hideki; Okazaki, Ken; Murakami, Koji; Kaneko, Takao; Higaki, Hidehiko; Nakashima, Yasuharu
Abstract : Aims: This study aims to investigate the effects of posterior tibial slope (PTS) on knee kinematics involved in the post-cam mechanism in bi-cruciate stabilized (BCS) total knee arthroplasty (TKA) using computer simulation. Methods: In total, 11 different PTS (0° to 10°) values were simulated to evaluate the effect of PTS on anterior post-cam contact conditions and knee kinematics in BCS TKA during weight-bearing stair climbing (from 86° to 6° of knee flexion). Knee kinematics were expressed as the lowest points of the medial and lateral femoral condyles on the surface of the tibial insert, and the anteroposterior translation of the femoral component relative to the tibial insert. Results: Anterior post-cam contact in BCS TKA was observed with the knee near full extension if PTS was 6° or more. BCS TKA showed a bicondylar roll forward movement from 86° to mid-flexion, and two different patterns from mid-flexion to knee extension: screw home movement without anterior post-cam contact and bicondylar roll forward movement after anterior post-cam contact. Knee kinematics in the simulation showed similar trends to the clinical in vivo data and were almost within the range of inter-specimen variability. Conclusion: Postoperative knee kinematics in BCS TKA differed according to PTS and anterior post-cam contact; in particular, anterior post-cam contact changed knee kinematics, which may affect the patient's perception of the knee during activities. Cite this article: Bone Joint Res 2020;9(11):761–767.